2022
DOI: 10.1080/07853890.2022.2048064
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled metabolic markers and relevant dysregulated pathways of lung cancer: a pilot study

Abstract: Introduction The clinical application of lung cancer detection based on breath test is still challenging due to lack of predictive molecular markers in exhaled breath. This study explored potential lung cancer biomarkers and their related pathways using a typical process for metabolomics investigation. Material and methods Breath samples from 60 lung cancer patients and 176 healthy people were analyzed by GC-MS. The original data were GC-MS peak intensity removing backg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In 2007, Chen et al highlighted the VOCs present in the headspace, and in another, much larger, study with 160 LC patients in 2021, found hexanal to once again rise to the level of a biomarker of LC [93]. Rudnicka et al [77], Gashimova et al [94], and Zou et al [100] also reported hexanal to be an EB biomarker of LC. Whereas Kischkel et al measured hexanal to have a greater median concentration in the EB of LC patients (0.59 nmol/L) than that of healthy smokers (0.31 nmol/L), the concentration in LC patients was less than the median concentration they measured in HCs (0.63 nmol/L) [68].…”
Section: Hexanalmentioning
confidence: 99%
“…In 2007, Chen et al highlighted the VOCs present in the headspace, and in another, much larger, study with 160 LC patients in 2021, found hexanal to once again rise to the level of a biomarker of LC [93]. Rudnicka et al [77], Gashimova et al [94], and Zou et al [100] also reported hexanal to be an EB biomarker of LC. Whereas Kischkel et al measured hexanal to have a greater median concentration in the EB of LC patients (0.59 nmol/L) than that of healthy smokers (0.31 nmol/L), the concentration in LC patients was less than the median concentration they measured in HCs (0.63 nmol/L) [68].…”
Section: Hexanalmentioning
confidence: 99%
“…Twenty-two discriminative VOCs were annotated, styrene being also found downregulated in LC patients who responded partially to treatment or remained stable ( Supplementary Table S3 ), along with two other VOCs (dodecane, 4-methyl and α-phellandrene) ( Nardi-Agmon et al, 2016 ). The second study ( Zou et al, 2022 ) selected 31 VOCs as biomarkers in the univariate analysis (UVA), which showed 0.787 AUC in the multivariate analysis (MVA) after cross-validation. Additionally, eight VOCs were found to be involved in a total of 18 metabolic pathways, of which 11 were significantly altered.…”
Section: Vocs In Exhaled Breath In Health and Pathologymentioning
confidence: 99%
“…Although many studies propose potential biomarkers for various pathologies, the expected clinical application of breath tests has not progressed as expected ( Buszewski et al, 2007 ; Sharma et al, 2023 ). Additionally, the link between potential biomarkers and specific pathologies is not clear ( Haick et al, 2014 ; Zou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These disruptions can signi cantly contribute to the development and progression of various diseases, including cancer [19][20][21][22][23] . Indeed, identifying inherited mutations in cancer-related pathways can provide valuable insights into the mechanisms involved in carcinogenesis, particularly in cases where patients have a comprehensive expositional history 24 . These inherited mutations become particularly relevant when dealing with extensive datasets, such as those generated from genome and exome sequencing 25,26 .…”
Section: Introductionmentioning
confidence: 99%